Timing of physical therapy for individuals with patellofemoral pain and the influence on healthcare use, costs and recurrence rates: an observational study - Jodi L. Young; Suzanne J. Snodgrass; Joshua A. Cleland; Daniel I. Rhon (BMC, 2021)
Abstract Background Early physical therapy has been shown to decrease downstream healthcare use, costs and recurrence rates in some musculoskeletal conditions, but it has not been investigated in individuals with patellofemoral pain. The purpose was to evaluate how the use and timing of physical therapy influenced downstream healthcare use, costs, and recurrence rates. Methods Seventy-four thousand four hundred eight individuals aged 18 to 50 diagnosed with patellofemoral pain between 2010 and 2011 in the Military Health System were categorized based on use and timing of physical therapy (first, early, or delayed). Healthcare use, costs, and recurrence rates were compared between the groups using descriptive statistics and a binary logit regression. Results The odds for receiving downstream healthcare use (i.e. imaging, prescription medications, and injections) were lowest in those who saw a physical therapist as the initial contact provider (physical therapy first), and highest in those who had delayed physical therapy (31-90 days after patellofemoral pain diagnosis). Knee-related costs for those receiving physical therapy were lowest in the physical therapy first group ($1,136, 95% CI $1,056, $1,217) and highest in the delayed physical therapy group ($2,283, 95% CI $2,192, $2,374). Recurrence rates were lowest in the physical therapy first group (AOR = 0.55, 95% CI 0.37, 0.79) and highest in the delayed physical therapy group (AOR = 1.78, 95% CI 1.36, 2.33). Conclusions For individuals with patellofemoral pain using physical therapy, timing is likely to influence outcomes. Healthcare use and costs and the odds of having a recurrence of knee pain were lower for patients who had physical therapy first or early compared to having delayed physical therapy.